2015
DOI: 10.1007/s10008-015-2898-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of self-doped copolymers of aniline with aminobenzensulfonic acids on stainless steel. Morphological and electrochemical characterization

Abstract: Self-doped conducting polyaniline (PAn) films were deposited on passive stainless steel (SS) AISI304 substrates by cyclic potential sweep deposition from aqueous mixed monomer solutions of aniline (An) and different aminobenzenesulfonic acids (2-, 3-or, 4-aminobenzenesulfonic acid, ABSA), without the presence of a supporting electrolyte. Two different An concentrations were examined (0.01 and 0.05 M), while the concentration of each ABSA used was kept constant at 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(94 reference statements)
1
4
0
1
Order By: Relevance
“…The weaker intensity of stripping signal at more negative potentials can be ascribed to the less conductivity of polyaniline along with the interruption of accumulation process by hydrogen evolution . The smaller stripping signal at more positive potentials may be due to the less reduction of copper ions and oxidation and eventually degradation of polyaniline . Cu(II) ions tend to form chelates with nitrogen, oxygen and sulfur atoms in the P(An‐co‐MA) membrane.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…The weaker intensity of stripping signal at more negative potentials can be ascribed to the less conductivity of polyaniline along with the interruption of accumulation process by hydrogen evolution . The smaller stripping signal at more positive potentials may be due to the less reduction of copper ions and oxidation and eventually degradation of polyaniline . Cu(II) ions tend to form chelates with nitrogen, oxygen and sulfur atoms in the P(An‐co‐MA) membrane.…”
Section: Resultssupporting
confidence: 79%
“…The P(An‐co‐MA) membrane was prepared using the potentiostatic method at a potential of +0.75 V. The aqueous growth solution consisted of 0.30 M of MA and 0.15 M of An without any additional supporting electrolyte. Such polymerization method and ratio of comonomers concentrations have been reported previously. It has been reported that preparation of conducting polymers without the presence of a supporting electrolyte, yield a polymer with more reproducible and well‐defined characteristics .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…P(Ani-co-3ABSA) coating was potentiostatically synthesized at a potential of 750 mV in an growth solution which solely composed of 0.15 M Ani and 0.30 M 3ABSA. Similar polymerization procedure [26] and concentration ratio of comonomers [27] have been used formerly. It has been recognized that synthesis of a conductive polymer in the absence of any supporting electrolyte produces a polymer coating with more favorable electrochemical properties [28].…”
Section: Electrochemical Synthesis and Investigating Morphology Of Thmentioning
confidence: 99%